Synthesis of acalabrutinib loaded β-cyclodextrin-based metal–organic frameworks as a potential material for breast cancer therapy - Mohammed F. Aldawsari; Md. Khalid Anwer (Results in Chemistry)
The current investigation successfully synthesized a porous β-cyclodextrin metal organic frameworks (βCD-MOFs). Herein, acalabrutinib (ACB) loaded βCD-MOFs (ACB-MOF) was engineered to improve the efficacy of ACB for the treatment of breast cancer. The ACB-MOF exhibited a particle size (627 nm) PDI (0.245) and EE (79.25 %), respectively. The developed ACB-MOF was characterized by fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), thermogravimetric analyzer (TGA) and nitrogen gas adsorption. In-vitro release studies exhibited an improved stability and release pattern for 24 h, with korsmayer-peppas kinetics model. ACB-MOF exhibited improved cytotoxicity and lowered IC50 (11.68 μg/mL) against MCF7 cells as compared to pure-ACB (25.01 μg/mL). The ACB-MOF also improve the level of apoptotic markers significantly (P53, caspase-3 and caspase-9), indicating a promising delivery for breast cancer.